Associations between childhood maltreatment and emotion processing biases in major depression: results from a dot-probe task - Günther, Vivien (BMC Psychiatry, 2015)
BACKGROUND: Childhood maltreatment is considered an important risk factor for the development of major depression. Research indicates an association between childhood adversity and altered emotion processing. Depression is characterized by mood-congruent cognitive biases, which play a crucial role in symptom persistence and recurrence. However, whether attentional biases in adult major depression are associated with experienced childhood neglect or abuse remains unclear. METHODS: A sample of 45 patients suffering from major depression were recruited to examine correlations between maltreatment experienced during childhood and attentional biases to sad and happy facial expressions. Attention allocation was assessed using the dot-probe task and a history of childhood maltreatment was measured by means of the 25-item Childhood Trauma Questionnaire (CTQ). RESULTS: Our results indicate an association between childhood maltreatment and sustained attention toward sad facial expressions. This relationship was not confounded by severity of symptoms, age, verbal intelligence or more recent stressful experiences. CONCLUSIONS: Our findings confirm the hypothesis that a mood-congruent bias in emotion processing observed in major depression is related to early traumatic experiences. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-015-0501-2) contains supplementary material, which is available to authorized users.